Exploring the Connection Between Peer Support and Emotional Loneliness Among Migrant University Students - Putri Syafa Laelatus Siam; Desi Maulia; Eka Sari Setianingsih (CV. Edujavare Publishing, 2026)
Living away from home often presents students with challenges in adapting to a new environment, which can potentially lead to emotional loneliness. This associative quantitative study aims to empirically examine the contribution of peer social support in reducing this condition. Using total sampling, all 101 eighth-semester students in the Guidance and Counseling program at PGRI University of Semarang for the 2025/2026 academic year were included as both the population and the sample. Data were collected using the Peer Social Support Scale (α = 0.910) and the Emotional Loneliness Scale (α = 0.889), which were then analyzed using Pearson’s product-moment correlation test. The results of the analysis showed a strong and significant negative relationship between the two variables (r = -0.606; p < 0.001). These findings confirm that an increase in peer support is directly proportional to a decrease in emotional loneliness, with the social support variable accounting for 36.7% of the variance in emotional loneliness.